2016
DOI: 10.1080/02640414.2016.1172723
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical investigation of right-forward lunging step among badminton players

Abstract: This study presents the kinematics and plantar pressure characteristics of eight elite national-level badminton athletes and eight recreational college-level badminton players while performing a right-forward lunge movement in a laboratory-simulated badminton court. The hypothesis was that recreational players would be significantly different from elite players in kinematics and plantar pressure measures. Vicon motion capture and Novel insole plantar pressure measurement were simultaneously taken to record the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 33 publications
3
64
0
Order By: Relevance
“…Kinematic data were collected using an eight-camera Vicon motion capture system at a frequency of 200 Hz, based on previous experimental Plug-in-Gait protocols [24, 25, 28, 29], which ensured the validity and reliability of the tests. The marker set included sixteen markers (diameter of 14 mm), bilaterally located to the anterior-superior iliac spine, posterior-superior iliac spine (PSI), lateral thigh (THI), lateral knee (KNE), lateral tibia (TIB), lateral ankle (ANK), heel (HEE), and toe (TOE) [24, 25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinematic data were collected using an eight-camera Vicon motion capture system at a frequency of 200 Hz, based on previous experimental Plug-in-Gait protocols [24, 25, 28, 29], which ensured the validity and reliability of the tests. The marker set included sixteen markers (diameter of 14 mm), bilaterally located to the anterior-superior iliac spine, posterior-superior iliac spine (PSI), lateral thigh (THI), lateral knee (KNE), lateral tibia (TIB), lateral ankle (ANK), heel (HEE), and toe (TOE) [24, 25].…”
Section: Methodsmentioning
confidence: 99%
“…However, previous studies investigating badminton movement mainly focused on different movements or lunge movement directions without comparing movement characters between professional and amateur badminton participants [2428]. In this study, we hypothesised that amateur and professional badminton players exhibit differences in the forehand right-forward lunge movement and these differences in kinetics and joint moments make them prone to different injury mechanisms.…”
Section: Introductionmentioning
confidence: 93%
“…Motor unit action potentials could be registered non-invasively by using surface electromyography. It has been stated several times that the muscle activation patterns depend on several aspects like training level and osteoarthritis (Benedetti et al, 2003;Knoop et al, 2012;Mei et al, 2017). The integration of electromyography and kinetic data could help to declare aberrant kinetic patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Based on an alpha of 0.05 and 80% power, 11 subjects per group were recruited for this study. In addition, previous studies investigating badminton lunges between elite and intermediate players have reported their findings based on eight participants with significant group mean differences of lower limb biomechanics variables [24]. For elite participants, they were practicing with national team training at Korean National Sports University and other universities in Seoul.…”
Section: Methodsmentioning
confidence: 99%